2023
DOI: 10.1126/science.adh0301
|View full text |Cite
|
Sign up to set email alerts
|

Conserved γδ T cell selection by BTNL proteins limits progression of human inflammatory bowel disease

Robin J. Dart,
Iva Zlatareva,
Pierre Vantourout
et al.

Abstract: Murine intraepithelial γδ T cells include distinct tissue-protective cells selected by epithelial butyrophilin-like (BTNL) heteromers. To determine whether this biology is conserved in humans, we characterized the colonic γδ T cell compartment, identifying a diverse repertoire that includes a phenotypically distinct subset coexpressing T cell receptor Vγ4 and the epithelium-binding integrin CD103. This subset was disproportionately diminished and dysregulated in inflammatory bowel disease, whereas on-treatment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(3 citation statements)
references
References 81 publications
0
3
0
Order By: Relevance
“…We also found that the vast majority of mucosal CD4 -MAIT cells express CD103 (integrin αEβ7), which adheres to the E-cadherin molecule expressed by intestinal epithelial cells [76]. While IBD has been associated with a lower percentage of dendritic cells [77], CD8 and CD4 T cells [78] and γδ T cells [79] expressing CD103, we saw no such thing in MAIT cells (Fig 2D ), and by fluorescent intensity we actually found a higher per-cell expression of CD103 protein on the CD103+ MAIT cells of IBD biopsies, regardless of inflammation (Fig 2E). Although analyses of histological morphology were outside the scope of this study, the CD103 + phenotype of intestinal MAIT cells (Fig 2D ) and their relative depletion from de-epithelialized colon lamina propria preparations (Fig 2F) suggests that they are intra-epithelial lymphocytes (IEL), in close proximity to the intestinal lumen, and thus the gut microbiome.…”
Section: Plos Onementioning
confidence: 61%
“…We also found that the vast majority of mucosal CD4 -MAIT cells express CD103 (integrin αEβ7), which adheres to the E-cadherin molecule expressed by intestinal epithelial cells [76]. While IBD has been associated with a lower percentage of dendritic cells [77], CD8 and CD4 T cells [78] and γδ T cells [79] expressing CD103, we saw no such thing in MAIT cells (Fig 2D ), and by fluorescent intensity we actually found a higher per-cell expression of CD103 protein on the CD103+ MAIT cells of IBD biopsies, regardless of inflammation (Fig 2E). Although analyses of histological morphology were outside the scope of this study, the CD103 + phenotype of intestinal MAIT cells (Fig 2D ) and their relative depletion from de-epithelialized colon lamina propria preparations (Fig 2F) suggests that they are intra-epithelial lymphocytes (IEL), in close proximity to the intestinal lumen, and thus the gut microbiome.…”
Section: Plos Onementioning
confidence: 61%
“…Nonetheless, compared to Cy3 + HA − or Cy3 − HA − γδ T cells, Cy3 + HA + γδ T cells exhibited lower CD3ε and TCRδ expression levels ( Fig. 4 C ), which is indicative of prior antigenic exposure ( 57 ).…”
Section: Resultsmentioning
confidence: 97%
“…Prior studies have shown that BTNL3 binds to Vg4+ T-cell receptors in a manner akin to superantigens 70 . Crucially, there is evidence that BTNL3’s role in selecting and maintaining γδ T cells is significant in curbing the progression of complex intestinal diseases that cause tissue damage 14 . This finding is particularly relevant, given that many of the common risk alleles associated with genetic predisposition to SLE are found in genes related to the immune system.…”
Section: Resultsmentioning
confidence: 99%